Ethics and medicolegal issues in Oral Pathology - Shrestha, Bijayata (Journal of Gandaki Medical College-Nepal, 2025)
Limited consideration is given for existence of code of ethics in Oral Pathology as they are stereotyped as working with only inert tissues and are removed from direct patient contact. However, there is a good amount of evidence to consider ethics in oral pathology. Commonly encountered ethical issues were related to the use of tissue for research, confidentiality/privacy issues, diagnosis errors, and medicolegal issues. Guidelines have been suggested in the existing literature for maintaining quality and ethical practice in histopathology. Recommendations are given in the literature, following which would make the process of reporting more standardized, which may contribute to patient care. Considering this, it is recommended to introduce Ethics in the Oral Pathology curriculum and encourage the Oral Pathologist to make this a way of life.